Olanzapine-induced weight gain is associated with the -759C/T and -697G/C polymorphisms of the HTR2C gene. - Godlewska, B; Olajossy-Hilkesberger, L; Ciwoniuk, M; Olajossy, M; Marmurowska-Michałowska, H; Limon, J; Landowski, J (2009)
Weight gain, a serious problem associated with some antipsychotic drugs, notably olanzapine and clozapine, was suggested to be associated with -759C/T polymorphism of the 5-HT2C receptor gene. This study aimed to examine a potential association of two functional polymorphisms of the promoter region of this gene: -759C/T (rs3813929) and -697G/C (rs518147), with weight gain after 6 weeks of olanzapine monotherapy. It included 107 patients with schizophrenia; among them 36 are first-episode drug-naive patients. Analysis was carried out by PCR-restriction fragment length polymorphism. A protective effect of -759T and -697C alleles was found: significantly less patients with -697C (3/51) and no patient with -759T (0/28) alleles experienced body mass index increase >or=10% (P=0.0006 and 0.002, respectively). The same was true for drug-naive patients possessing any of the variant alleles. There was a significant association of haplotypes with a >or=10% body mass index increase (P=0.001). On the basis of the additional statistical analysis, the more important role of -697C allele was suggested.